A Case of Ceftriaxone-Induced Acute Generalized Exanthematous Pustulosis/Generalized Pustular Psoriasis Overlap - Jianfeng Zheng; Yunlu Gao; Xuemei Yi; Yangfeng Ding (Karger Publishers, 2018)
Acute generalized exanthematous pustulosis, characterized by subcorneal or superficial intraepidermal pustules, is induced by drugs in more than 90% of cases. Psoriasis is an autoimmune disease triggered by different conditions in genetically susceptible people. Generalized pustular psoriasis is an acute and severe clinical form of psoriasis, which usually occurs in patients with psoriasis undergoing aggravating factors. In this report the authors have reported a 40-year-old male patient with primary syphilis who developed generalized pustular dermatosis after the use of ceftriaxone. On the third day after ceftriaxone treatment, complete regression of the syphilis lesions was reached. While on the sixth day, erythematous pustular lesions accompanied with fever were observed on the whole body. A personal history of psoriasis and histopathological findings with psoriasiform changes and subcorneal pustule favored the diagnosis. After discontinuation of ceftriaxone, the patient's condition slowly improved until he had plaque-type psoriasis 3 weeks later. A heterozygous c.115 + 6T>C missense substitution of IL36RN related to the pathogenesis of acute generalized exanthematous pustulosis/generalized pustular psoriasis was identified.